Validasi terhadap rubrik sebagai alat pengukuran penulisan ilmiah melalui penskoran kendiri pelajar terhadap tugasan (Validation of rubrics as an academic writing measurement tool through students' self-scoring of assignment) - Noor, Norzalina; Janan, Dahlia; Arshad, Mahzan (Universiti Utara Malaysia Press, 2019)
Purpose - This study explored changes in the quality of students’ academic writing and the consistency of scoring between students and examiners, to validate rubrics as a measurement tool for academic writing. Methodology – A pre-experimental single-group design with probability sampling was employed. Two lecturers from a Malaysian university scored academic writing samples of 122 students from two different groups using the same rubric. Intraclass correlation coefficients (ICC), limit of agreement (LOA) and standard error of measurements (SEM) were used to examine the agreement between examiners’ and students’ scores. Findings – It was found that there was a change in the quality of students’ academic writing between the initial and final draft, based on the increase in students’ self-assessment scores. The data further indicated that in terms of agreement, reliability was rather low, although still considered satisfactory, with evenly low LOA values. Importance - This study points to the importance of engaging students in the assessment process to increase their understanding of assessment criteria and expectations of lecturers, especially for courses with subjective forms of assessment.